Price discrimination and copyright law: Evidence from the introduction of DVDs - Julie Holland Mortimer (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
This paper examines the welfare effects of intellectual property protection, accounting for firms' optimal responses to legal environments. I examine firms' use of indirect price discrimination in response to U.S. copyright law preventing direct price discrimination. Using data covering VHS and DVD movie distribution, I explain studios' optimal pricing strategies under U.S. copyright law, and determine optimal pricing strategies under E.U. copyright law, which allows for direct price discrimination. I find that studios' use of indirect price discrimination benefits consumers and harms retailers. Optimal pricing under E.U. copyright law further benefits studios and consumers. I also reanalyze these issues assuming continued DVD adoption.
Keywords: 330